2023
DOI: 10.3390/microorganisms11061519
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activity of Selenium Nanoparticles against Food-Borne Pathogens

Abstract: Selenium is an essential micronutrient for all mammals and plays an important role in maintaining human physiological functions. Selenium nanoparticles (SeNPs) have been shown to demonstrate antioxidant and antimicrobial activity. The objective of this study was to explore whether SeNPs have the potential to be used as food preservatives with which to reduce food spoilage. SeNPs were synthesized through ascorbic acid reduction of sodium selenite (Na2SeO3) in the presence of bovine serum albumin (BSA) as a capp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…The size, shape, and surface charge of CoNPs can enhance their interaction with bacteria, resulting in increased antibacterial activity [ 21 ]. SeNPs also exhibit antibacterial capabilities; however, they may not be as efficient as CoNPs in producing ZOIs [ 22 ]. This variation could be attributed to changes in the mechanism of action, with SeNPs potentially exhibiting less reactivity or a decreased affinity for binding to bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The size, shape, and surface charge of CoNPs can enhance their interaction with bacteria, resulting in increased antibacterial activity [ 21 ]. SeNPs also exhibit antibacterial capabilities; however, they may not be as efficient as CoNPs in producing ZOIs [ 22 ]. This variation could be attributed to changes in the mechanism of action, with SeNPs potentially exhibiting less reactivity or a decreased affinity for binding to bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors demonstrated that a high surface area allows an enhanced antimicrobial effect [ 40 ]. The charge status of NPs also has a significant impact on their affinity to bacterial cell membranes and their subsequent entry into the bacteria [ 41 ]. The current study found that AgNPs-1 possesses a higher contact surface area and a zeta potential below −30 mV, which indicates its high stability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that until a nutritional plateau is reached, Se is specifically incorporated into selenoproteins, while at higher concentrations, excess Se becomes toxic through nonspecific incorporation, which leads to the formation of selenylated proteins that destabilize reactive oxygen species (ROS) homeostasis [ 74 ]. By colony-forming unit (CFU) analysis after SeNPs treatment, it was reported in a previous study that in the case of S. aureus , the CFU at 0 µg/mL SeNPs was 68.0 ± 11.5 and decreased to 57.8 ± 13.4 after 0.5 µg/mL SeNPs treatment, followed by an increase up to 74.4 ± 9.8 at 1 µg/mL SeNPs, with a subsequent decrease down to 51.8 ± 11.3 at 2.5 µg/mL SeNPs, then reaching 63.0 ± 17.3 at 5 µg/mL SeNPs with a significant decrease down to 39.2 ± 5.7 at 10 µg/mL [ 75 ]. However, even if there were some interesting variations, the effect noted in the aforementioned research was not statistically significant up to 10 µg/mL SeNPs.…”
Section: Discussionmentioning
confidence: 99%